Improving the Efficiency of Vγ9Vδ2 T-Cell Immunotherapy in Cancer - Hoeres, Timm; Smetak, Manfred; Pretscher, Dominik; Wilhelm, Martin (Frontiers in Immunology, 2018)
Increasing immunological knowledge and advances in techniques lay the ground for a more efficient and broader application of immunotherapies. γδ T-cells possess multiple favorable anti-tumor characteristics, making them promising candidates to be used in cellular and combination therapies of cancer. They recognize malignant cells, infiltrate tumors and depict strong cytotoxic and pro-inflammatory activity. Here we focus on human Vγ9Vδ2 T-cells, the most abundant γδ T-cell subpopulation in the blood, which are able to inhibit cancer progression in a variety of models in vitro and in vivo. For therapeutic use they can be cultured and manipulated ex vivo and in the following adoptively transferred to patients, as well as directly stimulated to propagate in vivo. In clinical studies Vγ9Vδ2 T-cells repeatedly demonstrated a low toxicity profile but hitherto only modest therapeutic efficacy. This review provides a comprehensive summary of established and newer strategies for the enhancement of Vγ9Vδ2 T-cell anti-tumor functions. We discuss data of studies exploring methods for the sensitization of malignant cells, the improvement of recognition mechanisms and cytotoxic activity of Vγ9Vδ2 T-cells. Main aspects are the tumor cell metabolism, antibody dependent cytotoxicity, antibody constructs, as well as activating and inhibitory receptors like NKG2D and immune checkpoint molecules. Several concepts show promising results in vitro, now awaiting translation to in vivo models and clinical studies. Given the array of research and encouraging findings in this area, this review aims at optimizing future investigations, specifically targeting the unanswered questions.